Minuman Probiotik Kombucha Dengan Ekstrak Daun Teh Hijau Sebagai Herbal Alternatif Untuk Meningkatkan Sistem Kekebalan Imun Tubuh - Dody Riswanto; Usman Setiawan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
Decreased body immunity has an impact on various kinds of disease disorders that attack the human body. Decreased body immunity is caused by one of the reasons for the wrong consumption of foods and beverages that contain cholesterol, fat, artificial sweeteners, preservatives, MSG, and other substances that are harmful to the body. To anticipate the body so that immunity remains well conditioned, healthy food is needed that is beneficial for the health of the body as a whole. Among these healthy foods is the fermented kombucha drink with green tea leaf extract. Kombucha is a probiotic drink made from fermented sweet tea and scoby microbial culture. The kombucha fermentation process generally takes between 7-14 days. The results showed that kombucha in terms of color, which is bright yellow after going through the fermentation process for 14 days. kombucha in terms of aroma, namely sweet and sour aroma with a sour smell that is very dominant compared to the sweet smell. Kombucha in terms of taste, which is sweet and sour with a sour taste that tends to be more dominant than sweet taste. Kombucha according to several research results that were reviewed based on chemical procedures, can increase the body's immune system. This is because kombucha contains antioxidants and vitamins that can stimulate the immune system to increase, among the antioxidants contained are polyphenols and several vitamins, especially vitamin B.